The Mstislav's Svytoslavich Alan marriage in the masage of the Ipatiev chronicle - Abukov S.N. (Cultural Heritage and Modern Technologies)
The article is devoted to the report of the Ipatiev chronicle on the marriage of the Chernigov prince Mstislav Svyatoslavich with Alan women. This unique monument of the South Russian chronicle is one of the main sources on the history of Ancient Russia. Analyzing this news of the chronicle, data from other sources, as well as the opinions of researchers, the author came to the conclusion about the reliability of the chronicle message. The marriage of Mstislav of Chernigov was of great importance not only in the system of family ties of the Olgovichi, but also Russian-Alan relations of the XII-XIII centuries, which must be considered in the broader context of the relationship between Russia and the steppe.